Novel TiO2/GO/M-MMT nano-heterostructured composites exhibiting high photocatalytic activity - Li, W.; He, Y.; Bao, W. B.; Bao, H. L.; Li, D. Y.; Zhang, C. L.; Wang, M. (Frontiers in Chemistry, 2023)
This study proposed a technique to enhance the photocatalytic properties of TiO2 using graphene oxide (GO) and modified Montmorillonite (M-MMT). TiO2/GO/M-MMT nano-heterostructured composites were prepared via hydrothermal and co-precipitation. The photocatalytic performance was evaluated by investigating the photodegradation rate and absorption behavior of methyl orange (MO) under visible light irradiation. The results showed that TiO2/GO/M-MMT heterojunction exhibited excellent photocatalytic degradation performance, as the degradation rate of MO was observed to be 99.3% within 150 min. The density of adsorbed MO decreased by 62.1% after 210 min of dark adsorption using the TiO2/GO/M-MMT composite, which was significantly higher than that achieved using M-MMT, GO/M-MMT, and TiO2/M-MMT. The nano-heterostructure increased the effective interface between TiO2, GO, and MMT, which increased the charge transfer ability and prolonged the electron-hole separation time. Therefore, the results of this study can be used to design novel photocatalysts to eradicate environmental pollutants.